Performance Optimization of A 4-Stroke Single-Cylinder Engine Through Intake Camshaft Profile Design Using a 1-D Simulation Cycle - MOHAMAD YUSOP, MUHAMMAD SYUKUR (Progress in Engineering Application and Technology, 2023)
An engine camshaft is a rotating shaft that operates an internal combustion engine’s intake and exhaust valves. Its primary function is to open and close the valves at the correct timing and duration to control the intake of air-fuel mixture and the expulsion of exhaust gases. The project objective is to construct a 1-D engine model to examine various camshafts for better performance for the standard engine. The subject of this study is a Yamaha B17 engine that has been used for the Yamaha Y15ZR motorcycle model. The engine is modelled in 1D simulation LOTUS ENGINEERING software in order to access the performances. The model is then correlated with the actual engine performance within the 4% discrepancy limit. The tuning of engine parameters comprises intake and exhaust camshaft profiles, which are the timing, lift, maximum opening point and duration. The second camshaft model, R2, underwent several modifications resulting in an increase of 0.2 Nm in torque and a rise of 0.5 kW in power at the specific engine speed. The optimization process demonstrated the effects of different camshaft profiles toward engine performance. The finding from the research study explores another method of optimization that unleashed the true engine performance.